(untitled) (Research, Society and Development, 2020)
Objective: To analyze the pattern of food consumption among adolescent students at a Federal Institute - in Rio Grande do Sul, Brazil. Methodology: 29 students from the first year of integrated high school of male and female and average age between 15 and 17 years participated. Food consumption was obtained through a self-administered quantitative food frequency questionnaire and in an electronic version. Results: It was observed that the dietary pattern of the adolescents studied was satisfactory. The daily energy intake of macronutrients is within the nutritional recommendations. And the consumption of food according to the degree of processing, also showed relevant results, as it had a low intake of processed foods and an increase in the consumption of fresh and minimally processed foods. Conclusion: Thus, the school environment is an important place for the formation of eating habits, since it is in this environment that adolescents remain for an expressive period of time, often full-time. Therefore, the importance of having integrated educational practices that address healthy eating as instruments to promote the health and quality of life of these students is highlighted.